The Influence of Financial Literacy on Mitigating the Use of Paylater in the Student Environment (Case Study in the Accounting Department of PSDKU Pontianak State Polytechnic, Sanggau Campus) - Syarif Muhammad Ilham; Edi Saputra; Muhammad Khairul Anam (CV Edujavare Publishing, 2026)
The rapid development of Buy Now Pay Later (BNPL) services as part of financial technology (fintech) innovation has provided greater convenience in digital transactions. However, it also increases financial risks when not accompanied by adequate financial literacy. This study aims to examine the effect of financial literacy, consisting of financial knowledge, financial attitude, financial behavior, and usage control, on the mitigation of Buy Now Pay Later (paylater) usage among students of the Diploma III Accounting Study Program at PSDKU Politeknik Negeri Pontianak, Sanggau Campus. This research employed a quantitative approach using a survey method. The sample was selected through purposive sampling, resulting in 22 respondents who had previously used pay later services out of a total population of 62 students. Data were collected using a Likert-scale questionnaire and analyzed with SPSS version 26 through descriptive analysis, validity and reliability tests, classical assumption tests, multiple linear regression analysis, partial hypothesis testing (t-test), simultaneous hypothesis testing (F-test), and coefficient of determination (R²) analysis. The findings indicate that all research instruments met the validity criteria, while most variables were found to be reliable. The partial test revealed that only the usage control variable had a positive and significant effect on the mitigation of pay later usage, whereas financial knowledge, financial attitude, and financial behavior did not have significant effects. Simultaneously, all independent variables significantly affected the mitigation of pay later usage, with an F-value of 10.288 and a significance level of 0.000. Furthermore, the coefficient of determination (R²) of 0.708 indicates that 70.8% of the variation in pay later usage mitigation can be explained by the variables included in the research model, while the remaining 29.2% is influenced by other factors outside the model. These findings suggest that students' ability to control their use of paylater services is the most influential factor in mitigating the financial risks associated with paylater usage.